SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI CAMPING BERDASARKAN KESULITAN TRACK DI SUMATERA UTARA DENGAN MENGGUNAKAN METODE TOPSIS - Fahrezi, Mhd Rio; Fakhriza, Muhammad (UIN Sumatera Utara Medan, 2023)
In the selection of camping sites and hiking areas, a system that could be used to help in the process of choosing a camping site with some criteria, a budget ora budget, a number of people, a certain amount of time to spend, as well as the altitude of MDPL, the humidity of a field, and a camping site. The system is built using the latter method for others, solutions for others to be identical to the ideal solution (topsis) category, the multi-alternative decision making (MCDM), which is the technique of several available alternative options for establishing the best alternatives, particularly multi, making decision (madm) in the problem-solving process that it hopes will help and support for making decisions made by decision-makers. The selection of outdoor tools and results from this system will be a list of reports of outdoor equipment for camping and hiking that match the camping site. The system will later produce results of outdoor equipment and any preparations to make camp.